KEKUATAN HUKUM ALAT BUKTI ELEKTRONIK DALAM PERUSAKAN HUTAN BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN PEMBERANTASAN PERUSAKAN HUTAN DALAM PEMBUKTIAN DI PERSIDANGAN - ', Yulastri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Environmental crime happened a long time and occurs every year in Indonesia. Efforts to deal with forest destruction has actually been carried out, but it is not effective and have not shown optimal results. This was partly due to the legislation that is not explicitly criminalize forest destruction is done in an organized manner. Therefore, the necessary legal protection in the form of legislation that organized the destruction of forests can be managed effectively and efficiently and providing a deterrent effect to the perpetrators. regulation of electronic evidence in the destruction of the woods yet firmness and not run well. Because of the Code of Criminal Procedure has not explicitly regulate the electronic evidence is valid, although the development of legislation after KIitab Law on Criminal Procedure Law indicates the integrity to manage electronic evidence.The purpose of this study to find out the settings of the power of the law of electronic evidence and the legal electronic evidence in forest destruction in accordance with Law No. 18 Year 2013 on the Prevention and Eradication of forest destruction in evidence during the trial.Electronic evidence can be regarded as an extension of letters or instructions, which is the legal evidence can be presented in court and the judge satelah perform legal discovery and stated that electronic evidence is valid evidence and legally defensible and have legal force as evidence.Crime forest destruction that increasingly sophisticated. Law enforcement and the community in order to balance the sophistication of the crime. Or law enforcement agencies in charge of prevention and eradication of forests in order to further jelih to prove the criminal destruction of forests such as monitoring or prevention of the destruction of forests by using a faster technology to determine the occurrence of a crime of forest destruction.Keywords: Evidence-Electronic-Forest Destruction of Evidence At Trial.